PJMHS 2022
DOI: 10.53350/pjmhs22163542
|View full text |Cite
|
Sign up to set email alerts
|

Nephro Defensive Efficiency of Cichorium Intybus Against Toxicity Caused by Copper Oxide Nanoparticles

Abstract: The penetration of nanotechnology into the medical world is constantly growing, and this raises concerns about its toxicity. This study aimed to illustrate the defense ability of Cichorium intybus (CI) against the nephrotoxicity induced by copper oxide nanoparticles (CuONPs) in a rat model. 32 laboratory rats were evenly distributed into 4 groups, each containing 8 animals. CON rats did not receive any dosage, whereas, CuONPs animals were dosed with copper oxide nanoparticles. As for the CuONPs + CI group, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The total RNA extraction kit from Vivantis, Malaysia, was employed for this purpose. Following the confirmation of RNA concentration and purity, the process of RT-PCR was conducted with M-MuLV reverse transcriptase (NEB#M0253) . The SYBR green PCR Master Mix (Thermo Scientific, Cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total RNA extraction kit from Vivantis, Malaysia, was employed for this purpose. Following the confirmation of RNA concentration and purity, the process of RT-PCR was conducted with M-MuLV reverse transcriptase (NEB#M0253) . The SYBR green PCR Master Mix (Thermo Scientific, Cat.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has been observed that they are afflicted with specific neurodegenerative disorders . CuO-NPs toxicity causes elevation of several oxidative stress biomarkers as well as histopathological alterations in vital organs, including the brain and the liver. , The brain exhibits increased susceptibility to oxidative stress due to its elevated concentration of polyunsaturated fatty acids (PUFA) and limited presence of antioxidant enzymes in comparison to other organs inside the body . CuO-NPs possess the ability to traverse biological barriers, such as the blood-brain barrier (BBB), owing to their minuscule dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…These particles have been exploited with unparalleled merit in various biotechnology and medical applications [2,3] due to their small size and larger surface area to volume ratio [4], in addition to their unique physical, chemical and electrical properties [5]. NPs are used in many consumer products, as paints and ceramics [6], as well as in cosmetics, which has become popular in the current era [7], in addition to being recruited as a new delivery system for drugs [8], biosensors [9], and cancer treatment [10]. The growing application of MNPs has led to an increasing release of these materials into the environment, threatening human life and other living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to CuO-NPs induces the elevation of different oxidative stress markers [16,17], raising the intracellular enzymes activities as transaminases and alkaline phosphatase (ALP), causing cellular leakage and loss of cell membrane functional integrity [18], and histopathological deviations in several organs, including the liver [9,19].…”
Section: Introductionmentioning
confidence: 99%